Proline-Rich Peptide from the Coral Pathogen Vibrio shiloi That Inhibits Photosynthesis of Zooxanthellae - Banin, Ehud (American Society for Microbiology, 2001)
The coral-bleaching bacterium Vibrio shiloi biosynthesizes and secretes an extracellular peptide, referred to as toxin P, which inhibits photosynthesis of coral symbiotic algae (zooxanthellae). Toxin P was produced during the stationary phase when the bacterium was grown on peptone or Casamino Acids media at 29°C. Glycerol inhibited the production of toxin P. Toxin P was purified to homogeneity, yielding the following 12-residue peptide: PYPVYAPPPVVP (molecular weight, 1,295.54). The structure of toxin P was confirmed by chemical synthesis. In the presence of 12.5 mM NH(4)Cl, pure natural or synthetic toxin P (10 μM) caused a 64% decrease in the photosynthetic quantum yield of zooxanthellae within 5 min. The inhibition was proportional to the toxin P concentration. Toxin P bound avidly to zooxanthellae, such that subsequent addition of NH(4)Cl resulted in rapid inhibition of photosynthesis. When zooxanthellae were incubated in the presence of NH(4)Cl and toxin P, there was a rapid decrease in the pH (pH 7.8 to 7.2) of the bulk liquid, suggesting that toxin P facilitates transport of NH(3) into the cell. It is known that uptake of NH(3) into cells can destroy the pH gradient and block photosynthesis. This mode of action of toxin P can help explain the mechanism of coral bleaching by V. shiloi.